Artificial Intelligence in Medical Imaging: The Beginning of a New Era - Nardi, Cosimo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Artificial intelligence is a term that refers to the ability to provide machines with human intelligence. In medicine it is becoming widely used. It finds application especially in the diagnostic and tumor fields. It is not yet able to replace the human brain, but several studies show how its support can be useful in making diagnoses and providing prognoses. This reprint addresses various satellite topics of this discipline, giving practical examples in various clinical fields. In addition, it highlights the strengths of this tool and proposes methods to improve its weaknesses by addressing issues such as increasing data sets and selecting the right features. It also addresses other innovative aspects that together with artificial intelligence can lead to improvements in surgery.